‘Sadaqahnow’ project business model: trusted fundraising mobile application for enhancing the well-being of local & global communities - Mohd Aini, Suraya Nabilah; Roslam, Siti Nur Idah; Nazuki, Nur Nadiah; Mohamad Helmi, Nur Fathnin Ilhami; Ahmad Dahlan, Abdul Rahman (IIUM Press, 2024)
This paper is to offer a conceptual business model (BM) for an IT project titled, ‘SadaqahNow.’ The project business model is developed to help addressing the challenges, extreme pains, essential gains, and important job-to-do of various customer segments, namely fundraisers and donors, when garned enough club donation funds. Adopting the design thinking (DT) methodology including conducting literature review (LR) and interviews to understand the key challenges, extreme pains, essential gains, and important job-to-do of the fundraisers and donors. Business modelling tools namely Business Environmental Map (EM), Business Model Canvas (BMC), and Value Proposition Canvas (VPC) are used to formulate, design, test, and establish the project business model. This is to ideate the initial project BM embedded with digital platform/apps, designed, and tested, The initial project business model, using the Business Model Canvas (BMC) framework, was validated by the customer segments via surveys – to validate the relevancy of the job-to-do, gain creators and pain relievers offering of the SadaqahNow project. Finally, the validated conceptual SadaqahNow project business model was established – offering potential solution in addressing the important job-to-do, as well as gain creators and pain relievers for fundraisers and donors. Future works include developing a detailed Project Implementation Plan for the development of SadaqahNow project.